Pompe disease: a country-wide molecular screening in a cohort of 15,068 study participants - Pushkov, Aleksander; Chudakova, Daria; Zhanin, Ilya; Nikitin, Sergey; Basargina, Elena; Kuzenkova, Lydmila; Andreeva, Daria; Vasil’eva, Maria; Vasichkin, Sergey; Gabitova, Albina; Gaisina, Elena; Saifullina, Elena; et al. (Frontiers in Molecular Biosciences, 2026)
IntroductionPompe disease (PD) is a rare inherited recessive autosomal disorder caused by pathogenic nucleotide variants within the gene GAA, encoding Acid alpha-glucosidase (GAA), the lysosomal enzyme catalyzing glycogen breakdown to glucose.MethodsWe performed molecular screening in a cohort of 15,068 participants with suspected PD of a wide range of age from several regions of Russia. Two screenings had been undertaken from 2014 to 2025, and 2021 to 2025, respectively: 13,128 patients were screened using “two-tier one-gene” algorithm (measurement of GAA activity in dried blood spots followed by Sanger sequencing of the GAA) and 1940 patients were screened using Next-Generation Sequencing (NGS)-based algorithm (NGS of the panel of genes linked to neuromuscular disorders, ANO5, CAPN3, DYSF, FKRP, SGCA, SGCB, SGCD, SGCG, TCAP, and GAA, followed by measurement of GAA activity when needed).Results63 causative nucleotide variants in the GAA gene were detected, the most common being c.-32-13T>G (28 patients) followed by c.2662G>T (10 patients). 25 novel nucleotide variants in the GAA gene were described. Of 1,940 patients screened using an NGS-based algorithm, 138 patients (7.1%) were diagnosed with various muscular dystrophies, myopathies, or PD. The majority of these individuals had biallelic variants in the CAPN3 gene (30%), indicative of calpainopathy. Total 57 (0.47%) and 8 (0.41%) patients were diagnosed with PD as a result of “two-tier one-gene” or NGS-based algorithms, respectively.DiscussionOverall, our study is the first large-scale country-wide selective screening for PD in Russia based on sequencing and GAA activity measurement and providing the most comprehensive overview of genetics of PD in this study population.